Pulmonary Rehabilitation in COPD: A Reappraisal (2008–2012) - Pierachille Santus; Linda Bassi; Dejan Radovanovic; Andrea Airoldi; Rita Raccanelli; Francesco Triscari; Francesca Giovannelli; Antonio Spanevello (Pulmonary Medicine)
Chronic Obstructive Pulmonary Disease (COPD) is a complex pathological condition associated with an important reduction in physical activity and psychological problems that contribute to the patient's disability and poor health-related quality of life. Pulmonary rehabilitation is aimed to eliminate or at least attenuate these difficulties, mainly by promoting muscular reconditioning. The scope of this paper has been the analysis of the literature on pulmonary rehabilitation in COPD patients has appeared in the last five years, focusing on the principal outcomes obtained. The results demonstrate that pulmonary rehabilitation has a beneficial effect on dyspnoea relief, improving muscle strength and endurance. Moreover, pulmonary rehabilitation appears to be a highly effective and safe treatment for reducing hospital admissions mortality and improving health-related quality of life in COPD patients. It represents, therefore, a very important therapeutic option that, along with standard pharmachological therapy, can be used to obtain the best patient management. The favourable results obtained with pulmonary rehabilitation programs should stimulate researchers to improve our understanding of the mechanisms that form the basis of the beneficial effects of this therapeutic intervention. This would in turn increase the effectiveness of pulmonary rehabilitation in COPD patients.